2016
DOI: 10.1007/s10113-016-1019-y
|View full text |Cite
|
Sign up to set email alerts
|

Sixty years of habitat decline: impact of land-cover changes in northern Italy on the decreasing ortolan bunting Emberiza hortulana

Abstract: Habitat loss and degradation are main global threats to biodiversity, and land-use changes in agriculture-dominated landscapes are crucial for an important portion of biodiversity, especially in Europe. We evaluated the effects of land-use changes on a threatened species, the ortolan bunting, in an agricultural area crucial for its conservation in Italy. We built a distribution model for ortolan bunting in current landscapes, and then re-projected it to past scenarios (1954 and 1999-2000). We evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Even if we cannot rule out the potential impact of land use change, and in particular of land abandonment (see e.g. Brambilla et al 2010Brambilla et al , 2017b, modelling results suggested an overwhelming importance of STI and thus a major impact of climate change.…”
Section: Discussionmentioning
confidence: 97%
“…Even if we cannot rule out the potential impact of land use change, and in particular of land abandonment (see e.g. Brambilla et al 2010Brambilla et al , 2017b, modelling results suggested an overwhelming importance of STI and thus a major impact of climate change.…”
Section: Discussionmentioning
confidence: 97%
“…tree alleys, shrubs, hedges, woody corridors, and small woodlots) that provide song-posts, foraging and nesting places (cf. Berg, 2008, De Groot et al 2010, Brambilla et al 2016, 2017). Shrub and woody vegetation within the agricultural landscape is an important habitat attribute for farmland wildlife (Hilty et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…A more heterogeneous landscape pattern, comprising the fine-scale mosaic of different agricultural and non-agricultural habitats with different management types, provides a high diversity of foraging and nesting resources (Benton et al 2003, Vickery and Arlettaz 2012). Landscape heterogeneity is known as a crucial factor in supporting populations of Ortolan Buntings (Vepsäläinen et al 2005, Deutsch and Sudbeck 2009, Berg 2012, Brambilla et al 2017) and other declining farmland birds (Haslem and Bennet 2008, Vickery and Arlettaz 2012, Šálek et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Calviño-Cancela et al 2012, Morán-Ordóñez et al 2012, 2013, Ramil-Rego et al 2013). In the context of ongoing land use change, the loss and fragmentation of heathlands may lead to difficult-to-reverse tipping points for species tightly linked to these habitats (Regos et al 2015, 2016, Brambilla et al 2017, Tapia et al 2017).…”
Section: Introductionmentioning
confidence: 99%